Tingkat Pengetahuan dan Sikap Masyarakat Tentang Pemanfaatan Tanaman Obat Keluarga (TOGA) Di Pekalongan - Andini, Indri; Oktaviani, Nila (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2026)
Family Medicinal Plants (TOGA) are a form of natural resource utilization that plays a role in community health maintenance efforts. The utilization of TOGA in the community is still influenced by the level of knowledge and attitudes of the community towards the use of medicinal plants. This study aims to determine the level of knowledge and attitudes of the people of Pekalongan City towards the utilization of Family Medicinal Plants. The research method used was quantitative descriptive research with a crosssectional approach. Sampling was conducted using purposive sampling with a total of 50 respondents. Data were collected using an online questionnaire and analyzed descriptively by calculating the percentage of respondents' answers. The results showed that most respondents had a sufficient level of knowledge, with ginger, turmeric, and lemongrass being the most widely known medicinal plants. The community's attitude towards the use of TOGA was generally good, indicating support for its use as an alternative in maintaining family health. However, the use of TOGA is still not optimal due to limited knowledge about proper processing and usage methods, as well as the availability of medicinal plants. Based on the results of the study, it can be concluded that the community has a positive attitude towards the use of Family Medicinal Plants, but increased education and socialization are still needed to support more appropriate and sustainable use of TOGA.